Strategy for Providing Feed to Sami Mupu Goat Farmer Group in Wanagiri Village, Buleleng Regency, Denpasar, Bali - Ni Ketut Mardewi; Luh Suriati; I Gusti Agus Maha Putra Sanjaya; I.W. Eka Putra Ariawan; I.M.Dedy Dharmika (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
During the coffee harvest season, coffee skins are generated as a byproduct of the coffee processing procedure. The quantity of coffee skin generated is substantial, typically 40% to 50%. Coffee skins are commonly subjected to a drying process and afterward provided to goats as a supplementary feed, typically without undergoing any specific treatment. The cellulose concentration of dried coffee skin is significantly elevated, which can lead to a decrease in its digestion. By employing technological advancements such as fermentation, it is possible to reduce the cellulose content or crude fiber present in coffee skins. This fiber reduction enhances the coffee skin's digestibility and shelf life. The utilization of fermented coffee skin as a concentrated feed source for goats has been observed. Based on scholarly sources, it has been suggested that goats require approximately 10% of their body weight in daily forage feed. Additionally, it is deemed essential to supplement their diet with concentrate feed, ideally amounting to 1% of their body weight, to offer additional nourishment. To sustain a population of 25-50 goats, each weighing an average of 25 kg, farmers are required to supply a daily feed quantity ranging from 75-125 kg. Therefore, group members must possess imperative for group members to possess an adequate provision of feed, including grass and concentrates, to consistently fulfill goats' dietary requirements the group to possess an adequate provision of feed, including both grass and concentrates, to fulfill the dietary requirements of goats consistently. One potential approach to addressing the challenges partners encounter is imparting knowledge, enhancing skills, and introducing suitable technology for by partners is imparting knowledge, enhancing skills, and introducing suitable technology to the strategic provision of goat animal feed. This can be achieved by fermenting coffee skins and producing silage, of fermenting coffee skins and producing silage, augmenting the feed's quantity and quality of the feed while extending its storage duration. The utilization of coffee skin waste, which is produced during coffee bean processing, as a viable feed option for goats is a promising solution. This approach eliminates the practice of stockpiling coffee skin waste beneath coffee trees, eliminates the practice of stockpiling coffee skin waste beneath coffee trees, and eliminates the practice of stockpiling coffee skin waste beneath coffee trees but also mitigates environmental pollution.